2012
DOI: 10.1111/j.1440-172x.2012.02035.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of empathy in undergraduate nursing students

Abstract: Empathy is a central component in effective healthcare provider-patient relationships, yet evidence exists that healthcare professions students lack empathy. A cross-sectional survey was completed to identify whether a relationship exists between empathy levels in baccalaureate nursing, psychology, pre-medical, pre-dental, pre-physical therapy, and pre-occupational therapy majors who have or have not identifi ed a projected specialty within their profession upon entry into practice, and compare these fi ndings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
52
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 28 publications
10
52
0
5
Order By: Relevance
“…Students also indicated that substance abuse problems were self-inflicted, irritating and difficult to work with and thus not as worthy of compassion or empathy. These results are similar to the findings of other MCRS studies that show students have the lowest regard for patients presenting with substance abuse problems (Boyle et al, 2010a(Boyle et al, , 2010bBrown et al, 2010;McKenna et al, 2011McKenna et al, , 2012.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Students also indicated that substance abuse problems were self-inflicted, irritating and difficult to work with and thus not as worthy of compassion or empathy. These results are similar to the findings of other MCRS studies that show students have the lowest regard for patients presenting with substance abuse problems (Boyle et al, 2010a(Boyle et al, , 2010bBrown et al, 2010;McKenna et al, 2011McKenna et al, , 2012.…”
Section: Discussionsupporting
confidence: 94%
“…Double-degree students showed an increase in regard towards patients presenting with intellectual disabilities, substance abuse and attempted suicide by their third year of study. Patients presenting with substance abuse had the lowest regard from paramedic students with is typical result found by other studies (Boyle et al, 2010a(Boyle et al, , 2010bBrown et al, 2010;McKenna et al, 2011McKenna et al, , 2012. Finally, this study demonstrates that females generally have a higher regard for patients presenting with intellectual disabilities, substance abuse and attempted suicide compared to their male counterparts.…”
Section: Discussionsupporting
confidence: 80%
“…Aunque pareciera no haber fundamento para decir si la empatía es una dimensión de la personalidad, una emoción experimentada o una habilidad observable, sí se sabe que involucra la habilidad de comunicar la comprensión del mundo del paciente. Por estas razones se sigue estudiando y, a pesar de que existe amplia información en la literatura que investiga la empatía, se considera a esta como un constructo clave como facilitador importante en las relaciones paciente-profesional del área salud (55)(56)(57), entre otros muchos complejos procesos involucrados en ella.…”
Section: Discussionunclassified
“…Araştırmamızda çocuk kliniklerinde çalışan hemşirelerin empatik eğilim puanlarının orta düzeyde olduğu tespit edilmiştir. Hemşireler ile ilgili empati çalışma-larında hemşirelerin empatik eğilim puanlarının çalışmamız ile benzer şekilde orta düzeyde olduğu görülmektedir (35 (30,(36)(37)(38)(39). Hemşirelik uygulamalarında empatiyi kullan-mak hastaların klinik ve sağlık çıktılarını pozitif yönde etkilemektedir.…”
Section: Discussionunclassified